Exoplanet Surveys at Universidad de Chile. Issue Volume 8:Issue S293(2012) (29th April 2014) - Rojo, Patricio; Jenkins, James; Hoyer, Sergio; Jones, Matías
Abstract: We present and highlight the first results of the three main exoplanet surveys we are currently conducting at Universidad de Chile: CHEPS, Red Giant Exoplanets (radial velocity), and TraMoS (transit lightcurves). We have several interesting candidates at the Calan-Hertfordshire Extrasolar Planet Search (CHEPS) project, which is aimed at searching for the currently missing southern bright transiting planets at a few m/s radial velocity precision. Using the same technique, we are also characterizing the planetary population in a constrained sample of Red Giant stars. The Transit Monitoring from the South (TraMoS) project is aimed both at improving transit parameters and at detecting any kind of lightcurve variability from several known southern exoplanet systems.